Higher Education Teaching Certificate Online Short Course - Vasquez Christodoulou, Marlen (My University, 2026)
How knowledge is constructed ▪ How learning works ▪ Building rapport ▪ Lesson planning and delivery ▪ Engaging students Course and assignment design ▪ Using feedback to improve your teaching ▪ Teaching portfolio preparation